The Effectiveness of Formal and Material Testing in the Constitutional Court's Decision on Law Number 11 of 2020 concerning Job Creation - Noval Nur Aditya; Putra Muhammad Zulfa; Rossa Avriliani; Widia Saraswati; Utang Rosidin (Regulate: Jurnal Ilmu Pendidikan, Hukum dan Bisnis, 2025)
This study examines the effectiveness of formal and material review conducted by the Constitutional Court of Indonesia (Mahkamah Konstitusi/MK) in safeguarding the constitutionality of laws, with a case study on Constitutional Court Decision Number 91/PUU-XVIII/2020 concerning Law Number 11 of 2020 on Job Creation. The research employs a library research method by analyzing relevant literature, academic journals, and court decisions. The findings reveal that the formal review highlighted significant procedural flaws in the legislative process of the Job Creation Law, particularly regarding the principles of transparency, public participation, and discrepancies between the approved and enacted texts. Consequently, the Constitutional Court declared the law conditionally unconstitutional, granting a two-year period for legislative improvements. Meanwhile, in the material review, most petitions were rejected as the contested provisions were considered part of the legislature’s open legal policy, despite concerns over labor rights protection and environmental sustainability. The effectiveness of Constitutional Court decisions in ensuring legal certainty largely depends on their compliance and implementation by lawmakers, as well as the extent of public dissemination. Thus, while the Court plays a vital role as the guardian of the constitution, its decisions still face challenges in practical enforcement.